μ-cf2vec: Representation Learning for Personalized Algorithm Selection in Recommender Systems - Tomás Trigueiros de Sousa Pereira (2020)
Collaborative filtering has becoming standard approach to achieve state of the art results in rec-ommendation systems problems. There are multiples implementations of this technique, each onethem with its own characteristics.